INDUCED VIABLE MUTANTS IN URDBEAN (VIGNA MUNGO (L.) HEPPER) - K. S. USHARANI,; C. R. ANANDA KUMAR, (The Bioscan, 2015)
The improved cultivar of urdbean namely VBN 4 were treated with single and combination dose/concentration of gamma rays (40kR, 50kR and 60kR) and ethyl methane sulphonate (EMS-50mM, 60mM and 70mM). The viable mutation frequency decreases with increasing doses of gamma rays. The highest frequency of mutants was recorded in 60mM (5.91 per cent) of EMS treatment followed by 60kR+60mM (5.88 per cent) of combination treatment. About 146 mutants were identified. High seed yielding superior plants as a result of increased number of pods ranging from 40-43 were observed in 40kR and 50kR of gamma ray and in 40kR+50mM, 40kR+70mM and 50kR+50mM of combination treatments when compared to the control (20-22 pods). Plants of bushy stature with condensed internodes when compared to control were found among the 50kR and 50mM of gamma ray and EMS population respectively. Dwarf types (10cm-16cm) were also identified among the 40kR, 60kR, 60mM, 70mM and 50kR+50mM, 50kR+60mM and 60kR+70mM population suited for lodging resistant. The present study reveals good scope for isolation of suitable morphological traits mutants induced may be useful in breeding programmes for the improvement of urdbean with agronomically desirable character which force is utilized in future breeding programme.